The Concept of Democracy An Essay on Conceptual Amelioration and Abandonment - Cappelen, Herman (Oxford University Press, 2023)
If we don't know what the words "democracy" and "democratic" mean, then we don't know what democracy is. This book defends a radical view: these words mean nothing and should be abandoned. The argument for abolitionism is simple: those terms are defective and we can easily do better, so let's get rid of them. According to the abolitionist, the switch to alternative devices would be a significant communicative, cognitive, and political advance. The first part of the book presents a general theory of abandonment: the conditions under which language should be abandoned. The rest of the book applies this general theory to the case of "democracy" and "democratic". The book shows that "democracy" and "democratic" are semantically, pragmatically, and communicatively defective. Abolitionism is not all gloom and doom. It also contains a message of good cheer: we have easy access to conceptual devices that are more effective than "democracy". We can do better. These alternative linguistic devices will enable us to ask better questions, provide genuinely fruitful answers, and have more rational discussions. Moreover, those questions and answers better articulate the communicative and cognitive aims of those who use empty terms such as "democracy" and "democratic".